2018
DOI: 10.1177/0886260518798354
|View full text |Cite
|
Sign up to set email alerts
|

Economic Policies and Intimate Partner Violence Prevention: Emerging Complexities in the Literature

Abstract: Although the question of whether economic policies serve to reduce rates of intimate partner violence (IPV) has long been raised, rigorous tests of this question have only begun to take place recently. Given the mixed evidence to date, much remains unknown about the circumstances in which a positive or negative relationship holds between changes in financial well-being and IPV. We describe an empirically based theoretical model that may link economic empowerment to IPV and that highlights research questions fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 65 publications
(94 reference statements)
1
16
0
Order By: Relevance
“…These heterogeneous findings align with other economic and social empowerment interventions for women that discovered heterogeneous or context-dependent effects [1–5]. For example, cash stipends improved long-term economic outcomes only for young women in settings where there are economic opportunities [1].…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…These heterogeneous findings align with other economic and social empowerment interventions for women that discovered heterogeneous or context-dependent effects [1–5]. For example, cash stipends improved long-term economic outcomes only for young women in settings where there are economic opportunities [1].…”
Section: Discussionsupporting
confidence: 66%
“…Economic interventions have recently caught the attention of public health researchers interested in social empowerment and intimate partner violence, thanks to the success of trials that have demonstrated widespread effects of cash transfers on social and health outcomes [2, 5]. Our research sounds a cautionary note on two grounds.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations